Injectability Evaluation: An Open Issue - Cilurzo, Francesco (Springer US, 2011)
The current work aimed to propose a system of scoring to rationalize and support the selection of the optimal diameter and length of needles. Four formulations at different viscosity and needles ranging from 21 to 26 G and length ranging from 16 to 40 mm were used. Plunger-stopper breakloose force, maximum force (F(max)), and dynamic glide force were measured by a texture analyzer at the crosshead speed of 1 mm/s. Testing was carried out into air or human subcutaneous tissue. The manual injectability of the highest viscosity product was assessed by ten evaluators. The comparison of the panel test score and the quantitative measurements of the forces permitted to score a given needle-syringe-formulation system keeping also in consideration the pressure created in the subcutaneous space and muscles at the injection site. In particular, the following relationship was drawn: at the F(max) up to 250 mPa, the injection was practically impossible; at F(max) ranging from 160 to 250 mPa, the injection was very difficult; at F(max) in the 125–160 mPa range, the injection was feasible, though with some difficulty; when the values of F(max) were lower 125 mPa, the injection went smoothly. On the basis of these preliminary data, a system of scoring the needle-syringe-formulation system is proposed to rationalize and support the selection of the optimal diameter and length of needles, keeping also in consideration the pressure created in the subcutaneous space and muscles at the injection site.